2010
DOI: 10.1117/12.864915
|View full text |Cite
|
Sign up to set email alerts
|

An oil film information retrieval method overcoming the influence of sun glitter, based on AISA+ airborne hyper-spectral image

Abstract: As an effective survey tool for oil spill detection, the airborne hyper-spectral sensor affords the potentiality for retrieving the quantitative information of oil slick which is useful for the cleanup of spilled oil. But many airborne hyper-spectral images are affected by sun glitter which distorts radiance values and spectral ratios used for oil slick detection. In 2005, there's an oil spill event leaking at oil drilling platform in The South China Sea, and an AISA+ airborne hyper-spectral image recorded thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Sun glitter, which is often confused for oil sheens, is problematic in visible remote sensing. Sun glitter can be reduced through signal processing techniques [ 9 , 10 ].…”
Section: Detection and Mapping Of Oil On A Water Surfacementioning
confidence: 99%
“…Sun glitter, which is often confused for oil sheens, is problematic in visible remote sensing. Sun glitter can be reduced through signal processing techniques [ 9 , 10 ].…”
Section: Detection and Mapping Of Oil On A Water Surfacementioning
confidence: 99%
“…Zhan et al used hyperspectral data from an oil spill to improve detection and purportedly calculate oil thickness [60]. They first corrected the data to remove sun glitter and then normalized the image.…”
Section: Spectral Differencesmentioning
confidence: 99%
“…In terms of spectral differences, several studies have reported the correlation between slick thickness and specific wavelengths ranging over the visible spectrum. However, researchers have reported different changes in spectral brightness or reflectance as a result of increased thickness and reached contradictory conclusion (Zhan et al, 2010;Ye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%